ANALISIS ETOS KERJA APARATUR SIPIL NEGARA (ASN) PADA SEKRETARIAT DPRD KABUPATEN KUTAI TIMUR - Satiti, Ghea Yuna (PREDIKSI, 2016)
This study aims to determine and describe the work ethic of civil state apparatus. The approach used in this study is a qualitative descriptive approach. In this research will be a description of the six indicators of work ethic, namely motivation, performance appraisal, organizational regulations, influence among fellow co-workers, supervision and coaching. The results showed that the general level of the State Civil Work Ethic Apparatus (ASN) in the Secretariat of the East Kutai Regency amounted to 83.95% and is currently on intervasl 76% - 100% or included in either category. Thus, the hypothesis formulated in this study can be verified.Â Â